HSP70 EXPRESSION AND BETHESDA CLASSIFICATION IN BUCCAL MUCOSAL CELLS OF RESIDENTS NEAR MEDAN LANDFILL: EKSPRESI HSP70 DAN KLASIFIKASI BETHESDA PADA SEL MUKOSA BUKAL PENDUDUK SEKITAR TPA MEDAN - Ramadansyah; T. Kemala Intan; Nadjib Dahlan Lubis; Causa Trisna Mariedina (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Chronic exposure to pollutants generated from landfill environments may induce oxidative and genotoxic stress in oral epithelial cells, while Heat Shock Protein 70 (HSP70) functions as a key cellular chaperone involved in maintaining proteostasis and mediating adaptive responses to environmental stressors. This study aimed to evaluate the association between HSP70 expression and the Bethesda 2014 cytological classification in buccal mucosal cells of residents living in proximity to the Terjun landfill in Medan, Indonesia. A cross-sectional analytical design was employed involving 100 adult participants, comprising 24 individuals residing within ≤1–3 km of the landfill and 76 residing ≥3 km away. Buccal epithelial samples were collected using sterile cytobrushes, examined using Papanicolaou staining, and assessed immunocytochemically for HSP70 expression using the Immunoreactive Score (IRS), categorized as low (≤4) or high (>4). Statistical analysis was performed with Fisher’s Exact Test at a significance level of p<0.05. The results demonstrated that 98% of samples were classified as NILM and 2% as ASC-US, with high cytoplasmic HSP70 expression identified in 5% of samples, predominantly among the exposed group; however, a statistically significant association was observed between HSP70 expression and Bethesda classification. In conclusion, the overall low HSP70 expression with slight elevation among exposed individuals suggests early adaptive epithelial responses to chronic pollutant exposure, supporting the potential role of HSP70 as a noninvasive biomarker for monitoring environmentally induced epithelial stress.